Hepatic transcriptome profiling unveils candidate genes in cattle with liver abscesses under the influence of beef genetics in dairy cattle. - Luana D Felizari; Sydney M Bowman; Chiquito J Crasto; Jhones O Sarturi; Dale R Woerner; Bradley J Johnson (PLoS ONE)
Liver abscesses are a significant concern in cattle feeding, linked to visceral condemnation and carcass trimming; however, the molecular mechanism of development and progression of liver abscesses is unknown. This study aimed to evaluate the hepatic transcriptomic profile, immunohistochemistry, and IGF-I circulation in beef × dairy (Angus × Holstein) steers with and without liver abscesses. Samples were collected from twelve steers (final body weight of 719 ± 5.8 kg) originating from the same feedlot and were selected based on liver scores at harvest. The animals were divided into abscessed (n = 6) and healthy livers (n = 6). Blood samples were used to measure circulating insulin-like growth factor I (IGF-I) levels using an ELISA kit. Liver samples were divided into two portions; one portion was used for immunohistochemistry (IHC) to identify IGF-I receptor (IGF-IR) abundance, while the second portion was used for RNA extraction, library preparation, and sequencing (Illumina NovaSeq 6000 platform). Differentially expressed genes (DEGs) were identified with the DESeq2 R package, using an adjusted p-value ≤ 0.05 and fold change > 1.5. Sera IGF-I was not affected by liver condition; however, IGF-IR abundance was up-regulated in abscessed livers. A total of 568 DEGs were identified, with 372 up-regulated and 196 down-regulated in abscessed livers. Notably, the most highly up-regulated genes were FGF23, NXPH4, and CYP7A1, while EPHA6, CD70, and INHBA showed the most significant downregulation. Protein-protein interaction (PPI) network analysis identified THBS1 and COL1A2 as significant hub genes. The DEGs showed enrichment in biological processes related to angiogenesis, cell migration, adhesion, and extracellular matrix organization. Pathway analysis indicated activation in signaling pathways, including hepatic fibrosis, interleukin, and IGF-I signaling. These findings reveal candidate genes and pathways linked to inflammatory responses and tissue remodeling, offering valuable evidence that enhances our understanding of the progression of liver abscesses in cattle.